« Moments of Vision » : l'écriture de Thomas Hardy - Stéphanie Bernard (Cahiers Victoriens et Edouardiens)
At the end of his career as a novelist, Hardy wrote dark stories, tragedies. The equivocal quality of these works can also be found in the poems : dealing with the loss of his wife Emma, the writer hesitates between the hope to find her again and the recognition of the inevitable failure of his quest, between the illusion of a second chance and the harsh acknowledgment of facts. The texts come close to evoking hallucinations. The visual quality of things is put into relief by Hardy's art. At the same time, the one who watches often loses himself or herself in the act of watching, by being absorbed into the object of his or her gaze. This object, often a woman, matters less for what it really is than for its power to attract and fix the gaze of the subject. What takes place in scenes like the beginning of The Return of the Native or the end of Tess of the D'Urbervilles is what Hardy called « moments of vision » in one of his poems. As the observer (usually a man) is seized by the object of his gaze, the visual screen that hides what is beneath the surface dissolves and a new mode of writing emerges. Poetic writing rises when words are unable to express the writer's meaning and when what is to be told is unspeakable, as it is the case with Tess's death or Jude's agony. Approaching the dark core of things with his obscure characters, Hardy eventually abandoned the novel and chose poetry. In his poems, he went on exploring the limbos of life, death and loss while shaping words into lyrical veils shading an unbearable truth.